Strategy to Improve Financing for Gold Installment Products at PT Bank Syariah Indonesia, Tbk. KCP Panyabungan - Ali Topan Lubis; Muhammad Safii Handika; Meliana Meliana; Muda Ahmad Siregar; Abdul Rasyid; Lahuddin Lahuddin; Khoirun Nisa; Ermadina Lubis; Amelia Dewita (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze the strategy for increasing gold installment financing at PT Bank Syariah Indonesia, Tbk., Panyabungan Branch Office. Gold installment financing is a financing service offered by Islamic banks to facilitate the public's ability to own gold as an investment instrument through an installment payment system in accordance with Sharia principles. This product is a popular investment alternative because gold has a relatively stable value and can be used as a form of long-term savings. This study used a qualitative approach with a descriptive approach. Data collection techniques included interviews, observations, and documentation with the bank and customers using the gold installment product. The data obtained were then analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the gold installment financing mechanism at PT Bank Syariah Indonesia, Tbk., Panyabungan Branch Office is implemented through several stages: the customer's financing application, the bank's feasibility analysis process, the execution of the contract, and the installment payments according to the agreed term. Strategies to increase gold installment financing include product promotions, improving customer service quality, and educating the public about gold investment and Islamic banking products. Furthermore, utilizing digital media is also a strategy to expand the reach of gold installment financing products to the public. This study also found that the increase in gold installment financing was influenced by several supporting and inhibiting factors. Supporting factors include high public interest in gold investment and the ease of the financing application process. Meanwhile, inhibiting factors include low public understanding of Islamic banking products and diverse economic conditions.